Adult intussusception: case reports and review of literature. Issue 953 (4th March 2005) - Yalamarthi, S; Smith, R C
Abstract : Adult intussusception occurs infrequently and differs from childhood intussusception in its presentation, aetiology, and treatment. Diagnosis can be delayed because of its longstanding, intermittent, and non-specific symptoms and most cases are diagnosed at emergency laparotomy. With more frequent use of computed tomography in the evaluation of patients with abdominal pain, the condition can be diagnosed more reliably. Treatment entails simple bowel resection in most cases. Reduction of the intussusception before resection is controversial, but there is a shift against this, especially in colonic cases. Surgical treatment can be difficult in gastroduodenal and coloanal intussusceptions, sometimes requiring innovative techniques. This paper presents the diagnosis and management of four cases of adult intussusception, followed by review of the literature.